Estimación del precio de indiferencia del carbono con la regeneración natural facilitada y la forestación de la encina y el alcornoque en montes mediterráneos (V Congreso Forestal Español, 2009)
En este estudio se comparan los costes de mitigar emisiones de carbono con la regeneración natural facilitada y la reforestación de dos especies típicas del monte mediterráneo: la encina y el alcornoque en cuatro sitios representativos de estos montes en España y Túnez. Se estiman los precios de indiferencia del carbono (en € tCO2 -1), incluyendo en el análisis costes y beneficios comerciales ligados a las dos inversiones forestales analizadas, y de forma adicional las actuales subvenciones a la gestión forestal. Los precios de indiferencia determinan el umbral mínimo de la compensación que requeriría un propietario forestal para aceptar llevar a cabo inversiones en la extensión y renovación del encinar o alcornocal. Los resultados de este análisis aportan nuevos argumentos para justificar un cambio en la actual preeminencia que las ayudas europeas dan al establecimiento de plantaciones forestales por mayores ayudas dirigidas a facilitar la regeneración natural de las masas forestales existentes que se encuentran proceso de degradación por envejecimiento. Palabras

La renta ambiental de los bosques (ARBOR Ciencia, Pensamiento y Cultura, 2008)
The objective of this paper is to show the measurement of the environmental income from two private Spanish forests, the Cork Oak Woodlands of the Alcornocales Natural Park (Cádiz and Málaga) and the Scotch Pine Forest of the Sierra de Guadarrama (Madrid and Segovia). We also contribute to the technical and political debate on governmental regulations of forest environmental accounting in European Union. We have measured the environmental goods and services consumed by private landowners and public visitors through the contingent valuation technique. We have estimated the value of mushrooms gathering by public visitors in the Scotch Pine Forests of the Sierra de Guadarrama taking the price and harvest from the mushroom market in Pinar Grande (Soria). The value for carbon estimated accounts for the avoided damage of the greenhouse effect mitigation due to the sequestration of the atmospheric carbon dioxide. The environmental valuations show that the private environmental profitability rates in the Alcornocales Natural Park and in the Sierra de Guadarrama are 2.13 % and 3.43 %, in relation to their corresponding land market prices. We have estimated that the total net values added are 1.63 and 3.28 times higher than its corresponding conventional net values added in the Alcornocales Natural Park and in the Sierra de Guadarrama.

Preferencias de los propietarios e intervención pública: el caso de las dehesas de la comarca de Monfragüe (Investigación Agraria: Sistemas y Recursos Forestales, 2003)
The public have an increasing interest in Dehesa environmental services (recreation, option and existence values). The growing Government incentives on environmental friendly agricultural practices have given a new opportunity for private economics of natural and environmental resources in Dehesa. This work presents the results from a Delphi questionnaire on owners’ preferences and demands of compensations for undertaking environmental conservation and improvement measures in Dehesa of Monfragüe shire. The private owners of Dehesa are investors that have, at the same time, commercial aims and private environmental services autoconsumption preferences. A contingent valuation questionnaire has been applied to a group of Dehesa ’ owners to measure the maximum willingness to pay (WTP) —to accept losses— of commercial capital income against the maintenance of private environmental services autoconsumption. The Delphi results show that owners’attitude is in favour to follow the environmental friendly agricultural practices, when the Government incentives are higher than the losses of commercial capital income plus a risk premium. The value of owners’ autoconsumption measured by the WTP question from the contingent valuation gives an autoconsumption profitability rate from 1% to 5% of the total market value of the Dehesa.

Aspectos económicos de las prácticas agroforestales: un sistema de indicadores monetarios y biofísicos (Cuadernos de la Sociedad Española de Ciencias Forestales, 2002)
Se presenta en este trabajo un sistema de Cuentas Económicas Agroforestales (CAF) que tiene como objetivos principales el cálculo de la renta total sustentable desagregada por aprovechamien- tos y la aportación de un grupo seleccionado de indicadores biofísicos del uso múltiple de los recur- sos naturales y ambientales de una tierra. La metodología CAF es desarrollada al hilo de su aplica- ción a una dehesa de la comarca de Monfragüe en el ejercicio contable del año 1997